Pengaruh Kualitas Pelayanan Terhadap Keputusan Pembelian Produk Lakeside Coffe - Siregar, Oktobeno Mikaila Hasudungan; Saputri, Marheni Eka (eProceedings of Management, 2024)
Service quality is one of the supporting factors for purchasing decisions. Service quality depends on the company'sability to provide satisfaction with its customers' needs. Meanwhile, a purchasing decision is an action carried out bya buyer towards a seller when choosing a product to buy. This research was conducted to determine the quality ofservice regarding purchasing decisions for Lakeside Coffee products, with 100 respondents used as the researchsample. To make it easier for researchers to carry out testing and data processing, researchers use SPSS software.The results of this research show that service quality has a positive effect on purchasing decisions. Service quality hasa significant influence on purchasing decisions.Keywords-service quality, purchasing decisions